Cytological Features That Differentiate Follicular Neoplasm from Mimicking Lesions - Kanghee Han; Hwa-Jeong Ha; Joon Seog Kong; Jung-Soon Kim; Jae Kyung Myung; Jae Soo Koh; Sunhoo Park; Myung-Soon Shin; Woo-Tack Song; Hye Sil Seol; Seung-Sook Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Background It is difficult to correctly diagnose follicular neoplasms (FNs) on fine-needle aspiration cytology (FNAC) because it shares many cytological features with other mimicking lesions. The aim of this study was to identify the cytological features that differentiate FNs from mimicking lesions. Methods We included the cytological slides from 116 cases of thyroid FN diagnosed on FNAC, and included their subsequent histological diagnoses. We evaluated the cytological architectural pattern and nuclear features of the lesions according to their histological groups. Results The final histological diagnoses of the 116 cases varied, and included 51 FNs (44%), 47 papillary thyroid carcinomas (40%) including follicular variant, and seventeen cellular nodular hyperplasias (15%). Regardless of the final histological diagnosis, microfollicular pattern was observed in most cases. On the other hand, trabecular pattern was identified in 34% of FNs, but not in any other lesions. Additionally, elongated nuclei and ground glass chromatin were found in only some papillary thyroid carcinomas. Conclusions This study shows that the trabecular pattern is a representative cytological feature of FNs that can be used to distinguish FNs from mimicking lesions. In addition, nuclear shape and chromatin pattern can be used to further confirm the diagnosis of FNs from mimicking lesions through FNAC.